The theory of complex network sensing. - Wang, Yidan. (2013)
Many real world systems undergo internal dynamics and at the same time, interact with variable environments. The objective of this project is to explore this interaction between internal dynamics and extrinsic information by simulating Ising spins on a scale-free network. As a first step to understand how complex networks sense and react to environmental signals, we studied how to achieve a global change of the system through the control of local nodes.